C# 7 and .NET Core cookbook : quick solutions to common programming problems with the latest features of C# 7.0, .NET Core 1.1, and Visual Studio 2017 /: quick solutions to common programming problems with the latest features of C# 7.0, .NET Core 1.1, and Visual Studio 2017. (2017) - Strauss, Dirk
No abstract available